Notes on the Collision between Fundamental Rights and the Proportionality Principle (Research, Society and Development, 2022)
The increase in the complexity of social relations and the changes in the conception of the State, together with the dominant democratic ideal, required the anticipation and protection, in our constitutional order, of a great number of Fundamental Rights. Thus, new problems arose for the realization of these rights and for the determination of the correct application of each one of them. The constitutional jurisdiction and the balance of interests for the resolution of conflicts between Fundamental Rights act in the sense of guaranteeing and effecting the Fundamental Rights foreseen in the Federal Constitution of 1988. The research was by the deductive method, corresponding to the discursive extraction of knowledge from general assumptions applicable to specific assumptions. Next, the argumentative-dialectical method will be used, in the form of a logic of persuasion. Through this method, we will seek to understand the juridical phenomenon that we intend to study, that is, to analyze the doctrinal positions on the subject to conclude that the constitutional jurisdiction and the balance of interests through the principle of proportionality for the solution of conflicts between Fundamental Rights are instruments that guarantee the supremacy of the Federal Constitution.